Cardiovascular system status in women with severe climacteric syndrome - N. V. Izmozherova; A. A. Popov; A. N. Andreev; A. V. Akimova; O. Yu. Stryukova; N. V. Tagiltseva; M. I. Fominykh; E. V. Kozulina (Российский кардиологический журнал, 2007)
The work was aimed at cardiovascular system status assessment in women with severe climacteric syndrome. This case-control study included 173 women with frequent hot flushes and 173 women without the symptom (control group). Anthropometry, lipid metabolism parameters, arterial hypertension (AH) and chronic heart failure rates were examined. Conclusion: severe, frequent hot flashes were associated with greater climacteric syndrome manifestation and higher rates of uncontrolled AH, resulting in diastolic heart failure.